Spirituality in Families Evaluated for Compulsory Hospitalization Due to Substance Use (Revista Iberoamericana de Bioética, 2026)
This study examines how spirituality is expressed among family members supporting patients with substance use disorders following discharge from involuntary hospitalization. It is an observational multiple case study with a qualitative approach, involving 31 follow-up consultations conducted at 30, 90, and 180 days. Participants’ statements were organized into three analytical categories: conditions for moving forward; the attribution of responsibility to others; and families’ reliance on religiosity. Expressions of spirituality emerged as a valuable resource for coping with and navigating these adverse situations. Post-psychiatric hospitalization care typically emphasizes medical consultations, medication adjustments, and symptom management, often overlooking alternative resources such as spiritual or religious factors. When used as a support strategy, spirituality strengthens the relationship between families and the care team and helps improve self-esteem, suggesting that this resource should be explored more extensively by healthcare professionals.
Keywords: spirituality; compulsory; disorders; family